ANALYSIS OF RIFFATERRE'S STRUCTURALISM-SEMIOTICS IN POEM “ON A GIRDLE” BY EDMUND WALLER - Saripi, Samid (ELLITE ( Journal of Education, Linguistics, Literature and Language Teaching), 2024)
Poetry is the art or work of the poet. The combination of experiences, poet's feelings, emotions, and thoughts is needed to create a good work. The language of poetry is different from the use of language in general. However, it must have an aesthetic value. The language of poetry comes from poetic elements. Therefore, researchers are interested in studying Rifatterre's theory of structuralism-semiotics using descriptive research methods using an objective approach that focuses on the intrinsic elements of poetry and Rifatterre's theory of structuralism-semiotics. The conclusion in this study is that there are intrinsic elements such as diction, figurative language, rhythm, rhyme, images and themes. Likewise, in the theory of structuralism-semiotics, the researcher finds out how the use of indirect expressions, heuristic readings and hermeneutics are needed to understand the meanings and signs in poetry